Control and evaluation of information resources by "container" curation - Urbano, Cristóbal (Anuario ThinkEPI, 2016)
In this article, we examine the need to re-interpret the control and evaluation of information resources in an environment of online searches and information use that is dominated by search engines and social networks. Taking into account the recent announcement of the end of the ALA´s prestigious Guide to reference, preceded several years ago by the disappearance of selective directories of web resources, including Intute, we explore the potential of content curation as a conceptual and methodological approach that can also be applied to the control and evaluation of quality information resources. These resources can be viewed as "containers" with a clear identity, whose "contents" experience a kind of dissolution within search engines and social networks. Here, we propose the concept of "container curation" as a method for evaluating and contextualising information resources within the realm of libraries and information literacy.
Keywords: Content curation; Container curation; Information resources; Reference resources; Evaluation; Libraries; Information literacy; Subject hubs; Library guides